Deconstructed Timeline: The New Figure of Time in “Burnt Norton” and “Slaughterhouse-Five” - Rojas Castro, Esteban (2018)
The following work draws a comparison between the images and symbols of time in T. S. Eliot’s “Burnt Norton” and Kurt Vonnegut’s “Slaughter- house-Five.” In spite of the texts’ different genres, styles and background, they express similar sentiments, and they match the use of several sym- bols. By doing so, they develop noticeably analogous concepts, such as ever-present time, the ambivalent relationship of humanity with the realm of possibility, and the overestimation of death.      En este artículo se hace una comparación entre las imágenes y símbolos del tiempo en “Burnt Norton” de T. S. Eliot y “Slaughterhouse-Five” de Kurt Vonnegut. A pesar de los géneros, estilos y trasfondos diferentes de los textos, ambos expresan opiniones similares y concuerdan en el uso de varios símbolos. Al hacer esto, desarrollan conceptos notable- mente análogos, tales como el tiempo presente perpetuo, la relación ambivalente de la humanidad con el reino de la posibilidad y la sobre- valoración de la muerte.